Dietary Interactions Between Threonine and Crude Protein in Diets for Growing Tom Turkeys 8 to 12 Weeks of Age - Waldroup, P.W.; Kersey, J.H.; Kidd, M.T. (International Journal of Poultry Science, 2002)
An experiment was conducted to estimate the Thr needs of male Large White turkeys from 8 to 12 week of age and to evaluate the effects of dietary CP on Thr needs. The dietary treatments consisted of a 2 x 6 factorial arrangement with two levels of CP (16.0 and 19.8%), each containing 0.50% total Thr by analysis. Aliquots of each CP basal diet were supplemented with L-Thr to provide total Thr levels of 0.50, 0.57, 0.64, 0.71, 0.78, and 0.85%. Initial and final bird weights were taken to determine BW gain; feed conversion ratios were calculated with adjustment for weight of birds that died during the study. Nonlinear and quadratic regression analyses were used to estimate a Thr requirement to optimize BW gain and feed conversion. For both BW gain and feed conversion, significant interactions were observed between dietary CP and Thr levels. Performance was superior for poults fed the low CP diet series, noted primarily at the lower levels of Thr. As levels of Thr reached a surfeit, no significant differences in performance were noted between poults fed the two CP levels. Using nonlinear regression analysis, dietary Thr levels of 0.68 (16.0% CP) and 0.76% (19.8%) were adequate for maximum BW gain while Thr levels of 0.61 (16.0% CP) and 0.70% (19.8%) were adequate for optimum feed conversion. However, when estimates were based on fitting a quadratic regression, dietary Thr levels of 0.83 (16.0% CP) and 0.98% (19.8%) were adequate for maximum BW gain, while Thr levels of 0.77 (16.0% CP) and 0.82% (19.8%) were adequate for optimum feed conversion. While the interactions between dietary CP and Thr may be interpreted to suggest that dietary CP levels influence amino acid requirements, the two basal diets were composed of protein sources that differ in digestibility of Thr. It is possible that the reduced BW gains and impaired feed conversion observed at the lowest level of Thr supplementation on the high CP diets were the result of a lower level of digestible Thr, rather than a direct influence of CP level per se.